Senescent cells exacerbate chronic inflammation and contribute to periodontal disease progression in old mice. Issue 10 (6th January 2021) - Aquino‐Martinez, Ruben; Eckhardt, Brittany A.; Rowsey, Jennifer L.; Fraser, Daniel G.; Khosla, Sundeep; Farr, Joshua N.; Monroe, David G.
Abstract: Background: Coinciding with other chronic comorbidities, the prevalence of periodontal disease increases with aging. Mounting evidence has established that senescent cells accumulate at sites of age‐related pathologies, where they promote "non‐microbial" inflammation. We hypothesized that alveolar bone osteocytes develop senescence characteristics in old age. Methods: Alveolar bone samples were obtained from young (6 months) and old (20 to 22 months) mice to evaluate the expression of senescence biomarkers by immunofluorescent staining. Osteocyte‐enriched fractions were used to characterize the age‐related senescence‐associated secretory phenotype (SASP) gene expression profile. Primary alveolar bone cells were exposed to the SASP via in vitro senescent conditioned media (SCM) administration. A multiplex assay confirmed protein levels of specific cytokines. Interactions with bacterial components were evaluated by stimulating cells with lipopolysaccharide (LPS). Results: Increased senescence‐associated distension of satellites (SADS) and p16 Ink4a mRNA expression were identified in alveolar bone osteocytes with aging. These findings were associated with increased levels of DNA damage, and activated p38 MAPK, both inducers of senescence. Furthermore, interleukin‐6 ( IL6 ), IL17, IGFBP4, and MMP13 were significantly upregulated with aging in osteocyte‐enriched samples. Interestingly, SCM potentiated the LPS‐induced expression of IL1α, IL1β, and IL6 . Cell migration and differentiation were also impeded by SCM. These in vitro effects were ameliorated by the p38 MAPK inhibitor SB202190. Conclusions: Accumulation of senescent osteocytes contributes to deterioration of the periodontal environment by exacerbating chronic inflammation and reducing regeneration in old age. Cellular senescence is a cell‐intrinsic response to DNA damage, and a host‐related mechanism associated with aging that could potentiate inflammation induced by bacterial components.